Impact of allergic symptoms on work productivity in allergic rhinitis: A MASK-air direct patient data study - Rafael José Vieira; Ana Margarida Pereira; Maciej Kupczyk; Frederico S. Regateiro; Desirée E. Larenas-Linnemann; Sanna Toppila-Salmi; Tomohisa Iinuma; Piotr Kuna; Alvaro A. Cruz; Luisa Brussino; Bilun Gemicioglu; Boleslaw Samolinski; et al. (Allergology International)
Background: Allergic rhinitis may impair work productivity. This study aimed to assess (i) the differential impact of allergic rhinitis symptoms on work performance, assessed by means of Visual Analogue Scale (VAS) work; and (ii) the effect of asthma comorbidity on work productivity. Methods: We assessed data from the MASK-air mHealth app of patients with allergic rhinitis. We identified factors associated with the impact of allergic symptoms on work productivity through multivariable linear mixed effects models. Results: We studied 260,378 days from 20,724 patients. In multivariable regression models, nasal symptoms showed the strongest association with VAS work (regression coefficient = 0.38 [95%CI = 0.38; 0.38]). Poor rhinitis control, measured by the combined symptom-medication score, was associated with worse VAS work (regression coefficient = 0.96 [95%CI = 0.96; 0.97]). The median VAS work in patients with probable or possible asthma (median = 9, interquartile range = 22 for probable and 23 for possible asthma) was greater than for patients with no evidence of asthma (median = 3, interquartile range = 12) (Cohen's d = 0.60). In patients with probable asthma, nasal and asthma symptoms showed a similar impact on work productivity (regression coefficient for VAS nose = 0.32 [95%CI = 0.31; 0.32]; regression coefficient for VAS asthma = 0.30 [95%CI = 0.29; 0.31]). Conclusions: Allergy symptoms, especially nasal symptoms, are associated with worse work productivity. In addition, patients with allergic rhinitis and asthma display more impairment in work productivity than patients with allergic rhinitis alone.